2012
DOI: 10.5504/50yrtimb.2011.0030
|View full text |Cite
|
Sign up to set email alerts
|

Drug Design by Regression Analyses of Newly Synthesized Derivatives of 8-Quinolinol

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Antimicrobial effects of 8HQ and its derivatives encompassing antibacterial,102104 antimalarial,105107 antiviral,108 antitubercular,109 and antidental plaque activities110,111 have been previously reported.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Antimicrobial effects of 8HQ and its derivatives encompassing antibacterial,102104 antimalarial,105107 antiviral,108 antitubercular,109 and antidental plaque activities110,111 have been previously reported.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, 8HQ derivatives were found to inhibit S. aureus strains 102. Quantitative structure-activity relationships (QSAR) study performed on 24 substituted 8HQ derivatives showed that ten three-dimensional descriptors such as molecular refraction (MR), partition coefficient (logP), total energy (E), standard Gibbs free energy (G), lowest unoccupied molecular orbital (LUMO), highest occupied molecular orbital (HOMO), total molecular energy (TotE), Wien index (WInd), Balaban index (BInd), and octanol-water ClogP were significant for the development of highly predictive ( R 2 = 0.988) model 102. Moreover, potent activity was found in ester derivatives rather than styryl derivatives 102…”
Section: Introductionmentioning
confidence: 99%
“… 28 Recently, the anticancer activity of 8HQ-based compounds has been reported. 29 33 Moreover, 8HQ and its derivatives exhibit a diverse range of biological activities, such as anti-neurodegenerative, 34 , 35 antimicrobial, 36 39 antimalarial, 40 42 antioxidant, 30 , 34 anti-inflammatory, 43 and anticancer activities. 44 …”
Section: Introductionmentioning
confidence: 99%